Near-infrared light for on-demand drug delivery. Issue 7 (13th June 2018) - Lim, Dong-Jin; Park, Hansoo
Abstract: There are currently many basic technologies for the controlled release of therapeutic molecules for the treatment of chronic pathologies such as arthritis, asthma, and diabetes. Examples of such technologies include selectively dissolvable capsules and tablets that are designed to respond to specific stimuli – such as pH, temperature, or specific enzymes – in a time-specific fashion. However, because of the biological variations between different individuals, which contribute to differences in the environments of therapeutic target locations, these technologies are not fully controllable. In the pursuit of drug-release technologies that are fully controllable, many approaches have been examined. One such approach involves the utilization of various light-sensitive molecules that are designed to release therapeutic agents when stimulated by light of specific wavelengths. Potential light sources that have been explored for this approach include ultraviolet (UV) and near-infrared (NIR) light. UV light, which exists in the range of 10–400 nm, is easily to utilize, and many chemicals and particles can be stimulated with light in this spectrum. Unfortunately, when used extensively – as would be the case for chronic pathologies – UV light can cause cellular damage at the molecular level, potentially leading to skin cancer. A viable alternative to UV light is NIR light, which offers deeper transdermal penetration and does not have many known adverse long-term side effects. Therefore, the purpose of this review is to investigate the use of NIR light and the associated therapeutic molecules for the controlled release of therapeutic agents in the potential treatment of chronic pathologies.